Frans de Waal's Conception of Genesis of Morality and Its Implications for Religious Pedagogy - Agnieszka Salamucha (Nicolaus Copernicus University in Toruń, 2016)
In my article, I present the statements about the genesis of morality from the evolutionary point of view, represented by social psychologists and other scientists, especially primatologists (Frans de Waal). The core of the discussion is the mental continuity between humans and (other) animals. I will discuss the controversy between so called "veneer theory" (moral tendencies/abilities are not created by evolution; human ancestors became moral by the rational choice) and "Russian doll theory/model" (the fundament of morality, empathy, is generated and developed by evolution). If we accept the thesis about evolutionary origins of human morality, do we still need in our individual and social life the idea of God as a holy lawgiver, governor and judge, which seems to be fundamental for religious pedagogy? If the sources of human morality are innate, how shall we change the idea of religious education?